STRATEGI PENGARUH DIFERENSIASI DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN KOPI DARI HATI JANJI JIWA DI KOTA PONTIANAK: STRATEGI PENGARUH DIFERENSIASI DAN CITRA MEREK - Muhammad Dwi Fitriyadi (J-MD Jurnal Manajemen Dakwah, 2022)
ABSTRACT Increasing the development of business and competition, demanding on innovation and creativity from all company leaders, to create products that have features of excellence and competitiveness. This research aims to find out, the influence of differentiation strategy and brand image, towards purchasing decisions of kopi dari hati janji jiwa in Pontianak City. Data Collection using purpose sampling, amounting as 100 respondents. The analysis tools used are the test of validity, reliability, analysis of multiple regression Linear, t test, f test, and coefficient of determination test. The results showed that partially the value of tcalculated > ttabel or 4.151>1,660, namely differentiation strategies had a significant effect on purchasing decisions, as well as brand image has significantly effect on purchasing decisions with the value of tcalculated >ttable, 7,729>1,660. Simultaneously differentiation strategies and brand image has significant effect on purchasing decisions with Fcalculate > F table,or 92,152>3.09, or indicated by a coefficient of determination of 65.5%.